Penolakan Fazlur Rahman terhadap hadis teknis pada hukum keperdataan - Idris, Abdul Fatah (Sekolah Tinggi Agama Islam Negeri Salatiga, 2013)
Muhammad SAW is a prophet that will be followed by his members. Therefore all what He said and didand His attitudes become a sunnah. However, after the prophet passed away, His hadith had developedbecause they were a verbal statement of the prophetâs sunnah done by the continuing generations. Untiltoday, there have been some hadith that have different pronunciation and interpretation. Such hadithmight be influenced by real condition of the environment. This discussion was directed towards FazlulRahmanâs perception on technical hadith in the civil law. Fazlul Rahman had a notion that technicalhadith was a hadith sourced from Muhammad SAW prophet, however, it was massively made by Hisfriends, either tabiâin or itbaâ tabiân. The method used in this review was historical approach methodand interpretative approaches that was generally used by historical tek-tek researcher, as prophetâs hadith.Or this research used term approach of asbab al-nuzul that was frequently done by salaf clergies. Thesignificance of this research was aimed to know Fazlul Rahmanâs conception on technical hadith on civillaw, and to find out his refusal reasons towars them. The research found the result that technical hadithon civil law was hadith produced from creative and dynamic interpretation method toward prophetâssunnah done by the continuing generation. Therefore, Fazlul Rahman refused the technical hadithbecause they were unhistorical and biographical hadith, and also, they were assumed as unscientifichadith. Furthermore, most of technical hadith contained of different opinion among clergies, so that itshowed the weakness of historical base. So, theoretically, technical hadith could be accepted by us asdiscourse of knowledge, but practically it often raised law controversy in the society.